A prospective longitudinal approach to examine the association between social position in childhood, adolescence, and adulthood with the control of hypertension during adulthood - Barradas, Susana; Lucumi, Diego I.; Mentz, Graciela; Agudelo, Diana Maria (Frontiers in Public Health, 2024)
Hypertension is one of the main concerns in public health, since it is related with increased morbidity, and potential years of life lost in addition to loss of quality of life. This study aimed to assess: (1) the distribution of indicators of life course SEP in a cohort of Colombian patients with hypertension and (2) to assess the association of life course SEP and control of hypertension among this cohort of patients. Data were obtained using the baseline survey of 258 patients from the Social Determinants and Inequities in the Control of Blood Hypertension Program (ProDSICHA). Mother occupation and housing conditions were measured with the Event History Calendar. Mother educational level was measured with the questionnaire developed by the Project on Ethnicity and Race in Latin America (PERLA). Socioeconomic position during adulthood was measured using education, occupation, and income level based in the MacArthur Network. In this sense, the group with a higher lifelong social position and the group of lower lifelong social position showed better control of hypertension (OR=1.21; p<.05; OR=1.33; p<.05, respectively) compared to those whose social position throughout life varied the most. No statistical differences were found in the relations between single lifetime social position variables, and hypertension control in the three time points analyzed. These findings warrant further research to deeper our understanding on the role of a multidimensional and cumulative approach of social position in hypertension control.